Acute Toxoplasma Gondii Infection in Cats Induced Tissue-Specific Transcriptional Response Dominated by Immune Signatures - Cong, Wei; Dottorini, Tania; Khan, Faraz; Emes, Richard D.; Zhang, Fu-Kai; Zhou, Chun-Xue; He, Jun-Jun; Zhang, Xiao-Xuan; Elsheikha, Hany M.; Zhu, Xing-Quan (Frontiers in Immunology, 2018)
RNA-sequencing was used to detect transcriptional changes in six tissues of cats, seven days after T. gondii infection. A total of 737 genes were differentially expressed (DEGs), of which 410 were up-regulated and 327 were down-regulated. The liver exhibited 151 DEGs, lung (149 DEGs), small intestine (130 DEGs), heart (123 DEGs), brain (104 DEGs), and spleen (80 DEGs)-suggesting tissue-specific transcriptional patterns. Gene ontology and KEGG analyses identified DEGs enriched in immune pathways, such as cytokine-cytokine receptor interaction, Jak-STAT signaling pathway, NOD-like receptor signaling pathway, NF-kappa B signaling pathway, MAPK signaling pathway, T cell receptor signaling pathway, and the cytosolic DNA sensing pathway. C-X-C motif chemokine 10 (CXCL10) was involved in most of the immune-related pathways. PI3K/Akt expression was down-regulated in all tissues, except the spleen. The genes for phosphatase, indoleamine 2,3-dioxygenase, Hes Family BHLH Transcription Factor 1, and guanylate-binding protein 5, playing various roles in immune defense, were co-expressed across various feline tissues. Multivariate K-means clustering analysis produced seven gene clusters featuring similar gene expression patterns specific to individual tissues, with lung tissue cluster having the largest number of DEGs. These findings suggest the presence of a broad immune defense mechanism across various tissues in cats against acute T. gondii infection.